Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/asna.200310250
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high‐frequency optical oscillation during the flare phase of EV Lac in 1999

Abstract: Abstract.A program of Many-sites Multi Channel simultaneous observations of flare stars by a network of telescops was initiated in 1998. The purpose of this program is to investigate the fine structure of the flares light-curve in UBVRI, depressing atmospheric and instrumental noises. In this paper we present the results of the observations on the Flare star EV Lac in the B color, which were carried out at the Stephanion observatory during the campaign of 1999. Discrete Fourier Transform analysis of the B-ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…It was found that transient high-frequency oscillations occurred during the flare event, and the observed frequencies (periods) ranged between 0.011 Hz (∼1.5 min) and 0.083 Hz (∼12 s). They found it in accordance with the results of the observation of transient optical oscillations on strong and medium flares (e.g Contadakis et al, 2004Contadakis et al, , 2012Contadakis, 2013,. and references cited there) Vida et al (2019b).…”
supporting
confidence: 87%
“…It was found that transient high-frequency oscillations occurred during the flare event, and the observed frequencies (periods) ranged between 0.011 Hz (∼1.5 min) and 0.083 Hz (∼12 s). They found it in accordance with the results of the observation of transient optical oscillations on strong and medium flares (e.g Contadakis et al, 2004Contadakis et al, , 2012Contadakis, 2013,. and references cited there) Vida et al (2019b).…”
supporting
confidence: 87%
“…The first application of the technique resulted in the discovery of HFO in brightness and colors of the detected flares (Zhilyaev et al 2000(Zhilyaev et al , 2003. Similar HFO of stellar flares were confirmed recently by Contadakis et al (2004). Here we present a complete colorimetric analysis of the two EV Lac flares detected during the multi-site monitoring in September 2004, processed with the digital filtering technique, analyzed with a set of the color-color diagrams, and considered in the network of a time-dependent phenomenological model of flares.…”
Section: Introductionsupporting
confidence: 60%
“…We identify the potential frequencies of the star's brightness oscillations from the power spectrum. To do this, we use the H o hypothesis test (see Contadakis et al 2004a), in which 𝜎 BN is used. 4.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…High-frequency, small-amplitude optical oscillations during a flare maximum of HII 2411 with a period of 14.4 s have been reported by Rodono (1974), while high-frequency optical oscillations of amplitude 10% in U and 2.5% in B and period 14.4 s on a flare of EV Lac around the flare maximum phase have been reported by Zhilyaev et al (2000). A multitude of high-frequency oscillations with amplitudes ranging between 1.4 and 2.6% and periods ranging between 6.9 and 20 s around maximum phase and the subsequent stages of the flare evolution of a flare on EV Lac have been reported by Contadakis et al (2004a). The resolution of the data was 1.2 s.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation